Cost-time profiling: Putting monetary measures onto value stream maps (2006)
The Cost-Time Profile (CTP) is a tool that presents graphically the accumulation, of direct costs on a product as it moves through the manufacturing process. CTP incorporates the time dimension, to the cost accumulation, and the area under the CTP curve is the Cost-Time Investment (CTI), which is a measure of the investment of resources on the manufacturing of the product. In this paper, a general overview of the CTP, its construction, applications and future research directions are presented.